2018
DOI: 10.3390/pathogens7010013
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Oral and Intravenous Mouse Models of Listeriosis

Abstract: Listeria monocytogenes is one of several enteric microbes that is acquired orally, invades the gastric mucosa, and then disseminates to peripheral tissues to cause systemic disease in humans. Intravenous (i.v.) inoculation of mice with L. monocytogenes has been the most widely-used small animal model of listeriosis over the past few decades. The infection is highly reproducible and has been invaluable in deciphering mechanisms of adaptive immunity in vivo, particularly CD8+ T cell responses to intracellular pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 111 publications
(153 reference statements)
1
15
0
Order By: Relevance
“…1F ). This is in line with the notion that > 90% of ingested bacteria are killed by gastric acids (Saklani-Jusforgues et al, 2000; Pitts and D’Orazio, 2018). Residual Lm in the intestinal lumen may have been degraded by digestive enzymes, or failed to cross the mucus layer of the intestinal epithelium or their tight junctions, or become cleared by peristaltic contraction and mucus secretion.…”
Section: Resultssupporting
confidence: 88%
“…1F ). This is in line with the notion that > 90% of ingested bacteria are killed by gastric acids (Saklani-Jusforgues et al, 2000; Pitts and D’Orazio, 2018). Residual Lm in the intestinal lumen may have been degraded by digestive enzymes, or failed to cross the mucus layer of the intestinal epithelium or their tight junctions, or become cleared by peristaltic contraction and mucus secretion.…”
Section: Resultssupporting
confidence: 88%
“…The i.p. route allows Listeria to disseminate systemically via the lymphatic system and blood, but it bypasses the need for invasion of the intestine, as occurs in oral infection (22). Previous work showed that the disruption of LTTR family members caused a loss of virulence.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the role of InlP1, InlP3, InlPq, and InlP4 in the pathogenesis in vivo , we used an oral mouse infection model that allows a close imitation of the natural transmission route and the host environment including gastric stress despite the higher deviation in CFU counts that accompanies oral infection. The CFU deviation is due to individual responses in the mice in comparison to intravenous infection based on the fact that orally acquired bacteria have to pass a series of bottlenecks to reach target organs for colonization (Pitts and D’Orazio, 2018). We explicitly did not use an intravenous mouse infection model because listeriosis is not initiated by high bacterial loads in the blood and the colonization of peripheral tissues can be affected by preliminary colonization of the gut which is entirely avoided when L. monocytogenes is applied intravenously (Pitts and D’Orazio, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The CFU deviation is due to individual responses in the mice in comparison to intravenous infection based on the fact that orally acquired bacteria have to pass a series of bottlenecks to reach target organs for colonization (Pitts and D’Orazio, 2018). We explicitly did not use an intravenous mouse infection model because listeriosis is not initiated by high bacterial loads in the blood and the colonization of peripheral tissues can be affected by preliminary colonization of the gut which is entirely avoided when L. monocytogenes is applied intravenously (Pitts and D’Orazio, 2018). In general, oral L. monocytogenes mouse infection models distort the species-specific invasion process of the primary entry site that relies on the interaction between InlA, the most important virulence factor during invasion, and E-cadherin, the corresponding receptor on epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation